Microscopic modelling of nematic elastic constants beyond Straley theory. Issue 3 (22nd December 2021) - Revignas, Davide; Ferrarini, Alberta
Abstract : We develop a method for the calculation of Frank elastic constants of nematics, which accounts for the coupling between the molecular shape and the director field in each deformation mode. Abstract : Recent findings on various classes of nematics, whose microscopic structure differs from the prototypical rod-like shape, evidence unusual elastic properties, which challenge existing theories. Here we develop a theoretical and numerical methodology for the calculation of Frank elastic constants, accounting for the coupling between the molecular shape and each specific deformation mode. This is done in the framework of Onsager–Straley's second-virial theory, using a non-local form of the orientational distribution function. The comparison between two benchmark systems, a straight and a bent rod, allows us to illustrate the distinct features of this approach, which include additional order parameters induced by the deformation and, related to this, an ideal contribution to the deformation free energy. Then, using a simple system that can be seen as a minimalist model of liquid crystal trimers, we discuss the impact of different molecular conformations on elastic constants.